PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI DINAS DAERAH PADA PEMERINTAH KOTA MATARAM - I GST. GEDE NARUNG (GANEC SWARA, 2023)
This study aims to 1) determine the effect of motivational variables which include the variable need for achievement, need for affiliation, and need for power which jointly affect the performance of Regional Office employees. 2) determine the influence of motivational variables partially affect the performance of Regional Office employees. 3) knowing the motivational variables that have a dominant influence on the performance of Regional Office employees in the Mataram city government. The type of research used is associative research with a population of 10,664 people with a sample of 73 people. Data analysis tools use Multiple Linear Regression with hypothesis testing tools using the F test (Simultaneous), t test (Partial) and Beta test (β) . Based on the results of the analysis and discussion of the results of the research, it can be explained that the motivational variables include: the need for achievement, the need for affiliation. and the need for power. jointly have a significant influence on the performance of Regional Office employees in the Mataram city government. This is indicated by the calculated F value of 3.731 which is greater than the F table of 2.74 at the 5% significance level. Whereas the variables need for achievement, need for affiliation, and need for power. partially has a significant influence on the performance of Regional Office employees in the Mataram city government. This is indicated by the t-count value of the independent variable which is greater than the t-table of 1.670 at a significant level of 0.05 or indicated by a significance level of <0.05. That the 'need for power' variable has a dominant influence on the performance of Regional Office employees in the Mataram city government. This is indicated by the highest Beta value of the independent variables, namely the need for power variable, which is equal to Beta = 0.354.